Arginine as a promising amino acid for functionalized nanosystems: Innovations, challenges, and future directions - Nie Lili; Li Yanwei; Xie Jianan; Lu Shan (Nanotechnology Reviews)
The amino acid arginine has been identified as a promising building block for the construction of functionalized nanosystems due to its unique chemical properties. Arginine-based peptides and polymers have been widely used in targeted drug delivery, gene therapy, and cancer therapy, as they can target specific cells and organs, thus increasing the efficiency and specificity of drug delivery. In addition, arginine-based nanosystems have shown potential in other applications such as imaging, regenerative medicine, environmental remediation, biosensing, gene editing, water treatment, and food safety. The synthetic methods for arginine-based nanosystems have been improved over the years, and new characterization techniques have been developed to properly evaluate the performance and properties of arginine-based nanosystems. However, several challenges need to be overcome to fully realize the potential of arginine-based nanosystems. These include scale-up and industrial production, biocompatibility and toxicity, and in vivo evaluation. In addition, the safety and toxicity of arginine-based nanosystems need to be carefully evaluated. This review covers recent progress in the field of arginine-based nanosystems, highlighting the advantages and limitations of arginine-based nanosystems as well as the current challenges and future perspectives in the field. It is an important source of information for researchers, scientists, and engineers working in the field of functionalized nanosystems, and it highlights the potential of arginine-based nanosystems in various applications and the challenges that need to be overcome to fully realize their potential.